2019
DOI: 10.1126/science.aay0240
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes as sources of emergent host phenotypes

Abstract: Microbial communities associated with animals exert powerful influences on host physiology, regulating metabolism and immune function, as well as complex host behaviors. The importance of host–microbiome interactions for maintaining homeostasis and promoting health raises evolutionarily complicated questions about how animals and their microbiomes have coevolved, and how these relationships affect the ways that animals interact with their environment. Here, we review the literature on the contributions of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
153
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(161 citation statements)
references
References 42 publications
5
153
1
2
Order By: Relevance
“…Recent advances in microbiome research revealed that the gut microbiome is not just a passive bystander, but actively impacts multiple host functions, including circadian rhythmicity, nutritional responses, metabolism and immunity. 3,4 The mammalian immune system encompasses a complex network of innate and adaptive components in all tissues, and plays a vital role in host defense against various potentially harmful external agents and endogenous perturbations of homeostasis. From an ecological perspective, mammals and their commensal microorganisms co-evolved toward mutualism and hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in microbiome research revealed that the gut microbiome is not just a passive bystander, but actively impacts multiple host functions, including circadian rhythmicity, nutritional responses, metabolism and immunity. 3,4 The mammalian immune system encompasses a complex network of innate and adaptive components in all tissues, and plays a vital role in host defense against various potentially harmful external agents and endogenous perturbations of homeostasis. From an ecological perspective, mammals and their commensal microorganisms co-evolved toward mutualism and hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota take part in many functional metabolic pathways to in uence nutrient digestion and absorption, lipid metabolism and hormone biosynthesis. These can, in turn, affect host behaviors such as social communication, stress response, cognition and feeding behavior [39]. Thus, we further analyzed the functional pathway enrichment to predict the in uence of the early social contact on the gut microbial functions of piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into human gut microbiome has revealed the pivotal role of microbial communities in host health and disease 1 , however the majority of the studied microbiome are from defecated feces, which are powerful representations of gastrointestinal (GI) microbial ecosystems yet still with limitations. Fecal microbiome largely represent the last stage of transitions of microbial communities along the GI tract, and as numerous biogeographical analyses revealed the distinction of fecal microbiome from different GI sections 2 , where important biological processes take place.…”
Section: Introductionmentioning
confidence: 99%